HOUSE OF REPRESENTATIVES INSURANCE CMTE STAFF ANALYSIS & ECONOMIC IMPACT STATEMENT BILL #: HB 1456 (Tufts Archival Research Center, 2007)
Staff analysis and economic impact statement of Florida House of Representatives, Insurance Committee, regarding HB 1456, banning smoking by fire fighters. Discusses impact of requirement for new fire fighter certification that recruits must have refrained from using tobacco and tobacco products for one year prior to application. Acknowledges that ban may reduce the number of fire fighter applicants and may pose constitutional issues.